Adhesion Improvement between PE and PA in Multilayer Rotational Molding - Sezemský, Jan; Špatenka, Petr (Polymers, 2021)
The aim of this study is to investigate a multilayer structure made of polyethylene and polyamide by rotational molding. Due to the different polarity of these polymers, it is difficult to ensure enough adhesion between created layers. Two methods leading to improve adhesion are introduced. Plasma modification of polyethylene powder, after which new functional groups are bound to the treated surface, may enhance specific adhesion by forming hydrogen bonds with-CONH groups of polyamide. Different strategies of adding material to the mold give rise to complicated interlayer which increases joint strength by mechanism of the mechanical adhesion. Mechanical tests show a significant improvement of joint strength, where treated samples reached two-fold values of peel strength (7.657 ± 1.024 N∙mm-1) against the untreated sample (3.662 ± 0.430 N∙mm-1). During bending test, delamination occurred only in samples that were made of the untreated polyethylene. Adding polyamide during the melting stage of polyethylene powder in rotomolding resulted in the formation of entanglements which improve the peel strength almost eight times in comparison with the sample where the polyethylene was left to completely melt and create smooth interlayer surface.
Keywords: plasma treatment; polyethylene; multilayer rotational molding; adhesion; polyamide